Development of Leader-Followers Leadership Model at MAN 2 Bengkulu City - Yunitasari Yunitasari; Syukri Hamzah; Sudarwa Danim (STKIP Taman Siswa Bima, 2023)
This study aims to describe the concept of Leader-Followers Leadership and the priority characteristics of leaders that must be possessed in developing Leader-Followers Leadership at MAN 2 Bengkulu City. This study uses an observation approach and a literature study to obtain information about the characteristics of a leader that must be possessed in developing leader-follower leadership. In this study, the data used were primary data with primary data collection techniques through observation with informants. Secondary data is also used in whose data collection technique is through literature study. Decision-making techniques to determine priority characteristics of leaders that must be owned in developing Leader-Followers Leadership using the weighting method. From the results of the research that has been done, Leader-followers leadership is a study that adopts Dunham and Pierce's leadership, known as Dunham and Pierce's Leadership. This leadership pays great attention to the leader, follower, context and outcome. All parts play a role in leadership and are interconnected and influence. This is necessary to build the culture of the Bengkulu City State Aliyah Madrasa (MAN) 2 so that they work together in advancing education and become one of the leading madrasas in the City of Bengkulu. Based on the results of calculating the Context criteria (C), it is a top priority to be developed to establish Leader-Followers Leadership at MAN 2 Bengkulu City with a weight of 28.07%. They are then followed by Outcome criteria (O) in second place with 25.85%, Leader (L) in third place with 24.61% and Follower (F) in fourth place with 21.46%.